The Challenges and Prospects of Enforcement of Nigeria’s Counter-Terrorism/ Insurgency Laws and Policies: Implications for National Security - Nte, Ngboawaji Daniel; Enoke, Brebina Kelvin; Omolara, Joda Adekunbi (The Indonesian Journal of International Clinical Legal Education, 2022)
Interpretation of legal guidelines can vary widely-relying at the occasions dealing with a rustic and its political structure-in different words, whether or not it's miles an autocracy or democracy. Acts of terrorism were described as moves intentionally fascinated by malice and the purpose to destabilize or wreck the essential political, constitutional, financial and/or social structure. The paper finds out that the country's anti-terrorism legislation is critical. The key law under consideration is the Terrorism Prevention (Amendment) Act 2013. The paper strongly suggests that in order for the Nigerian government to fulfil its counter-terrorism objectives, it must change its attention to tackling the underlying fundamental causes of terrorism. Furthermore, the work suggested that, for long-term sustainable solutions, the opportunity to engage-and address the concerns of-the entire population, including marginalized segments of the population who offer passive resistance to terrorist and outlaw groups, is at the heart of a successful counter-terrorism campaign. Most individuals are inclined to approve such a strategy if they can see evidence of success and can envisage even modest but progressive changes. It is only by their active participation and collaboration will the political leadership be able to capture the hearts and minds of the people, particularly Nigeria's youth, and act on the enormous prospects for Nigeria's economic, social, and intellectual advancement.